Factors affecting Earnings Management of Publicly Listed Companies: Indonesia Perspective - Sinaga, Judith T.G.; Purnama, Timothy (Fakultas Ekonomi Universitas Advent Indonesia, 2024)
The aim of this study is to determine the partial and simultaneous effects of firm size and institutional ownership on the earnings management of Indonesian publicly traded enterprises. Using a quantitative approach and causal associative research methodology, this study demonstrates the cause-and-effect relationship between independent and dependent variables by collecting and processing data to provide the knowledge required for analysis and problem-solving. Six distinct statistics comprise the data analysis employed in this study: regression analysis (multiple, simple), significant test (t, f), coefficient of correlation analysis (r), descriptive statistics analysis (mean, maximum, and minimum values), and coefficient of determination analysis (r2). The analysis result of the research is that, partially, there is no effect of firm size on earnings management and there is no effect of institutional ownership on earnings management. Simultaneously, there is no effect of firm size and institutional ownership on earnings management.